AVP1: One Protein, Many Roles. (February 2017) - Schilling, Rhiannon K.; Tester, Mark; Marschner, Petra; Plett, Darren C.; Roy, Stuart J.
Abstract : Constitutive expression of the Arabidopsis vacuolar proton-pumping pyrophosphatase (H + -PPase) gene ( AVP1 ) increases plant growth under various abiotic stress conditions and, importantly, under nonstressed conditions. Many interpretations have been proposed to explain these phenotypes, including greater vacuolar ion sequestration, increased auxin transport, enhanced heterotrophic growth, and increased transport of sucrose from source to sink tissues. In this review, we evaluate all the roles proposed for AVP1, using findings published to date from mutant plants lacking functional AVP1 and transgenic plants expressing AVP1 . It is clear that AVP1 is one protein with many roles, and that one or more of these roles act to enhance plant growth. The complexity suggests that a systems biology approach to evaluate biological networks is required to investigate these intertwined roles. Trends: The type I H + -PPase in Arabidopsis thaliana (AVP1) regulates both vacuolar acidification and cytosolic pyrophosphate (PPi ) concentrations. Expression of AVP1 increases the growth and yield of many transgenic plants under various abiotic stresses, including drought, salinity, and low phosphorus (P) and nitrogen (N) supply. Transgenic plants expressing AVP1 also have enhanced shoot and root biomass in nonstressed conditions. Various mechanisms have been proposed to explain the larger size of transgenic plants expressing AVP1, including increased vacuolar ion sequestration, improved auxin transport, enhanced heterotrophic growth, and increased transport of sucrose from source to sink tissues.